Influência do hipoclorito de cálcio na resistência de união de materiais restauradores à dentina coronária - Sala, Letícia (2019)
This work aimed to evaluate the influence of Calcium Hypochlorite (Ca(OCl)2) on the bond strength of restorative materials to coronary dentin. For this, 90 bovine mandibular central incisors were used, which were cut in order to expose the dentin of the pulp chamber. The specimens were randomly divided into 9 groups, according to the solution used. Ca(OCl)2 was used as an irrigant at concentrations of 0.5%, 2.5% and 6%, with or without EDTA. Sodium Hypochlorite (NaOCl) was also used at a concentration of 6%. A group with EDTA only and a control group that received no treatment. After being in contact with the substances of the respective groups, the dentin was etched with Phosphoric Acid 37% and Ambar adhesive was used for dentin hybridization. The restoration was performed with composite resin. Each specimen was cut in a metallographic cutter, thus obtaining the “sticks” that passed through a microtensile test. For statistical analysis, the ANOVA test was used followed by the Tukey test. The results show that the control group and the one irrigated only with EDTA were similar (P>0.05); the other groups were similar to each other (P>0.05) and statistically lower than the control group (P>0.05). From the results it can be concluded that NaOCl and Ca(OCl)2, regardless of the concentration used, negatively affect the bond strength of adhesive materials to dentin.